FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2011-2013 - Hasugian, Ridy Argi; Basri, Yesi Mutia; Silfi, Alfiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to examine the effect of Net Income, Operating Cash Flow and Growth Company of the Dividend Policy in Manufacturing Company. The population in this study were all manufacturing companies engaged in Manufacturing Industry in Indonesia Stock Exchange and using financial statements in 2011 and 2013 as many as 142 companies, but based on the above criteria there are only 26 companies. Data analysis method using multiple linear regression analysis. Based on the analysis, the conclusions of this research are: 1) Net Income has significant negative effect on the Dividend Payout Ratio (DPR); 2) Operating Cash Flow has positive and significant effect on the Dividend Payout Ratio (DPR); 3) Growth Company has significant negative effect on the Dividend Payout Ratio (DPR); and 4) The coefficient of determination is 19.2%, it means that 19,2% of dependent variable is affected by the independent variable, while 80.8% are influenced by variables outside of the variables examined in this study.Keywords : Dividend Policy, Net Income, Operating Cash Flow and Growth Company